Diagnostic Accuracy of Diffusion Weighted Magnetic Resonance in Differentiating Between Malignant and Benign Endometrial Soft-Tissue Lesions - Hina Hanif Mughal, Sana Yaqoob, Hina Hafeez Abbasi, Fizza Batool, Irum Qaiser (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Pathological variation and image overlapping due to several endometrial conditions could be challenging for radiologists. Diffused weighted magnetic resonance imaging (DWI) is a reliable and promising imaging technique for the diagnosis and characteristics of endometrial lesions. The present study aimed to assess the diagnostic accuracy of diffused weighted magnetic imaging resonance in differentiating between malignant and benign endometrial soft-tissue lesions. Methodology: This descriptive cross-sectional study was carried out on 50 suspected endometrial lesions in the department of radiology, Benazir Bhutto hospital, Rawalpindi from January 2021 to December 2021. Non-probability consecutive sampling technique was used for all the participants meeting the inclusion criteria. Patients were categorized into two groups; Group I and Group II comprised 25 suspected benign and malignant endometrial lesions respectively. All the study patients were subjected to ultrasound and MRI examination of the pelvis. DWI imaging was done and the ADC value was calculated at a high b value. Histopathological data was collected. Data were analyzed using SPSS version 23. Results: Of the total 50 endometrial lesions, histopathological results were divided into the malignant group (25 lesions, 50%) and benign group (25 lesions, 50%). Out of 50, 38 lesions (21/25 benign and 17/25 malignant lesions) were correctly diagnosed by the conventional magnetic resonance imaging technique. The sensitivity, specificity, predictive positive value (PPV), and negative-positive value (NPV) of conventional MRI were 76.82%, 79.41%, 74.12%, AND 81.5% respectively. However, combining the apparent diffusion coefficient (ADC) value at b=1000 with DWI, about 48 lesions (24/25 benign and 24/25 malignant lesions) were correctly diagnosed. The sensitivity, specificity, predictive positive value (PPV), and negative-positive value (NPV) of conventional MRI were 94.82%, 93.23%, 91.6%, and 97% respectively. Conclusion: Diffusion-weighted MRI can help in distinguishing uterine endometrial lesions as benign and malignant. The diagnostic accuracy of Combined DWI with ADC mapping is higher than conventional MRI when differentiating benign lesions from malignant lesions. Additionally, sensitivity, specificity, and accuracy of combined DWI with ADC mapping increased in pelvic MRI examination for differentiating endometrial focal lesions. Keywords: Pelvic ultrasound; MRI Pelvis; Benign and Malignant endometrial lesions, Validity.